Pengaruh Pembiasaan Gotong Royong Kebersihan terhadap Tingkat Kesadaran Ekologis Santri di Pondok Pesantren Diponegoro Bali - Muhammad Adz Dzahabie; Riza Ashfari Mizan; Zaenudin Mudaham Amin; Benny Prasetiya (Education Reserach Center, 2025)
This study aims to examine the effect of cleanliness-based mutual cooperation practices on students’ ecological awareness at Diponegoro Islamic Boarding School, Bali. The research employed a quantitative approach using an explanatory research design. The population consisted of 65 students, all of whom were included as the research sample. Data were collected through a Likert-scale questionnaire developed based on Pierre Bourdieu’s habitus theory and Stern’s Environmental Awareness Theory. The data were analyzed using classical assumption tests and simple linear regression with SPSS version 26. The findings indicate that cleanliness-based mutual cooperation has a very strong and significant effect on students’ ecological awareness, with a coefficient of determination of 80.6%. This result demonstrates that collective and consistently implemented social practices within the boarding school environment are highly effective in shaping students’ ecological awareness across cognitive, affective, and conative dimensions. In conclusion, the habituation of mutual cooperation in cleanliness activities represents an effective strategy for fostering ecological character education in Islamic boarding schools and holds strong potential to be developed as a sustainable, value based environmental education model grounded in Islamic principles.